Covid-19 Lockdown and Implicit Kidnapping in Abeokuta Metropolis: Emergency As a Global Prolongation of Human Rights Abuse - Haruna Ishola Abdullahi (International Journal of Community Service & Engagement, 2023)
There are a number of responses to Covid-19 emergency across the globe. One reaction to mitigate the dastardly effects of Covid-19 such as massive loss of lives is imposition of lockdown. This action was a similitude of indirect kidnapping of the citizenry. In the normal kidnapping, victims` freedom of movement is truncated. In the same vein, the enforcement of lockdown denies citizens of their right to movement. This has negative consequences for the fundamental human rights to association, work and dignity of person. Hence, this paper assessed the Covid-19 and implicit kidnapping of citizenry as an elongation of abuse fundamental right of movement in Abeokuta metropolis. The study was cross-sectional, it adopted both qualitative and quantitative research methods. Data were sourced primarily and secondarily. It anchors on anomie theory by Emile Durkheim and betrayal trauma theory by Jennifer Freyd`s. The sample size was gotten through Taro Yamane sample size formula. The questionnaires were administered to 500 re There are a number of responses to Covid-19 emergency across the globe. One reaction to mitigate the dastardly effects of Covid-19 such as massive loss of lives is imposition of lockdown. This action was a similitude of indirect kidnapping of the citizenry. In the normal kidnapping, victims` freedom of movement is truncated. In the same vein, the enforcement of lockdown denies citizens of their right to movement. This has negative consequences for the fundamental human rights to association, work and dignity of person. Hence, this paper assessed the Covid-19 and implicit kidnapping of citizenry as an elongation of abuse fundamental right of movement in Abeokuta metropolis. The study was cross-sectional, it adopted both qualitative and quantitative research methods. Data were sourced primarily and secondarily. It anchors on anomie theory by Emile Durkheim and betrayal trauma theory by Jennifer Freyd`s. The sample size was gotten through Taro Yamane sample size formula. The questionnaires were administered to 500 respondents. However, 440 was returned from the field, consequently the response rate was 88%. 312(70.90%) of the respondents were male, while 102(23.18%) were females. 102(94%). The results of the hypotheses tested: Analysis of Variance (ANOVA). The test statistic (0.1731 and 0.0980) exceeded the Pvalues (0.000 and 0.000). The alternative hypotheses that there are significant relationships between lockdown and fundamental human right abuse was accepted. The paper recommends effective compensation for victims of lockdown. It will be useful to individuals, organisation, government agencies and researchers in social sciences. spondents. However, 440 was returned from the field, consequently the response rate was 88%. 312(70.90%) of the respondents were male, while 102(23.18%) were females. 102(94%). The results of the hypotheses tested: Analysis of Variance (ANOVA). The test statistic (0.1731 and 0.0980) exceeded the Pvalues (0.000 and 0.000). The alternative hypotheses that there are significant relationships between lockdown and fundamental human right abuse was accepted. The paper recommends effective compensation for victims of lockdown. It will be useful to individuals, organisation, government agencies and researchers in social sciences.